Reduction of the risk of the corrosion of seawater mixed cement-based materials. - Olcay Gurabi Aydogan; Shaghayegh Sadeghzadeh Benam; Nilufer Ozyurt (Revista ALCONPAT)
Ultra-High-Performance Concretes are those concretes with notable characteristics in terms of compressive strength, durability, and ductility. These concretes emerged in the 1980s as a solution to the search for high durability through the implementation of particle packing models, to reduce the porosity and increase the densification level of the cement matrix, a feature that’s make them highly durable against various external potential deleterious agents. Currently, among the applications in which these concretes are being widely used, architectural applications are becoming increasingly more prominent, due to their versatility in adopting shapes, textures, finishes, etc. However, in these applications it will be advantageous to reduce the weight of the material, to improve its thermal conductivity, but ensuring that the material reach its compressive and flexural strengths within appropriate values for structural applications. To reduce the weight and to reach compressive and flexural strengths, this work evaluates the incorporation of expanded polystyrene perlite (EPP) in substitution by mass of a limestone sand (0, 30, 55, 80 and 100 %) and a synthetic PVA structural fiber. To evaluate the synergistic effect of the EPP and PVA in a UHPC cementitious matrix the following properties were examined: compressive strength, flexural strength, surface electrical resistivity, bulk electrical resistivity and thermal conductivity.